Liquid chromatography/mass spectrometric identification of benzimidazole anthelminthics metabolites formed ex vivo by Dicrocoelium dendriticum - Cvilink, Viktor; Szotáková, Barbora; Vokrál, Ivan; Bártíková, Hana; Lamka, Jirí; Skálová, Lenka (Rapid communications in mass spectrometry, 2009)
With further use of chemical agents in the control of parasitic infections, an increased number of drug resistance occurrences to antiparasitic drugs has been reported. Induction of enzymes responsible for detoxification of given drugs can contribute to drug resistance development in a parasitic organism. The identification of formed metabolites allows the characterization of the enzymes participating in biotransformation and possibly in drug resistance development. The objective of our work was to find and identify phase I and phase II metabolites of the anthelminthic drugs albendazole, flubendazole and mebendazole formed in ex vivo incubations by the parasitic helminth Dicrocoelium dendriticum, a parasite of ruminants and other grazing animals, using liquid chromatography/mass spectrometric (LC/MS) techniques. In the ex vivo study, approximately 50 living D. dendriticum adults were incubated in 5 mL RPMI-1640 medium in the presence of 10.0 micromol L(-1) benzimidazole drug (5% CO(2), 38 degrees C) for 24 h. The bodies of the parasite were then removed from the medium. After homogenization of parasites, both parasite homogenates and medium from the incubation were separately extracted using solid-phase extraction. The extracts were analyzed using LC/MS with electrospray ionization. The results showed that D. dendriticum enzymatic systems are capable of phase I oxidation and reduction as well as phase II conjugation reactions. Detected phase I metabolites comprised albendazole sulfoxide, reduced flubendazole and reduced mebendazole. As for phase II metabolites, methyl derivatives of both reduced flubendazole and reduced mebendazole were observed.
Keywords: Benzimidazoles; Anthelmintics; Chromatography, Liquid; Animals; metabolická inaktivace; chromatografie kapalinová; hmotnostní spektrometrie; zvířata; Dicrocoelium; anthelmintika; benzimidazoly; Mass Spectrometry; Inactivation, Metabolic